2022
DOI: 10.21203/rs.3.rs-1868697/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Cerebral Microbleeds on Lower and Upper Extremities Function in Cerebral Small Vessel Disease

Abstract: Background and Purpose: White matter hyperintensities (WMHs) , lacunars and brain atrophy have been demonstrated to be positively related to gait disorder. However, cerebral microbleeds (CMBs) as a manifestation of cerebral small vessel disease (CSVD) is still under-estimated. Therefore, we investigated the correlations between CMB and upper and lower extremity motor performance.Method: A cross-sectional study of middle-aged to older adults was conducted for this study. CSVD burden was measured with magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Cognitive function disorder ( n = 37) and normal cognitive function ( n = 107) patients were classified according to whether or not cognitive dysfunction occurred. The inclusion criteria were as follows: (1) Patients compatible with T2DM diagnostics criteria established by the ‘China Diabetes Prevention and Treatment Guideline (2017 Edition)”[ 11 ]; (2) patients who met the “Diagnostic Criteria of Lacunes” in the 2021 “Chinese Common Cerebrovascular Disease Medical Specialist Common Recognition” guidelines[ 12 ]; (3) routine blood tests performed on admission, and baseline data such as blood lipids and blood sugar levels were complete; and (4) head magnetic resonance imaging (MRI) was recorded on admission. The exclusion criteria were as follows: (1) Other intracranial diseases such as intracranial infection, massive cerebral infarction, cerebral hemorrhage, and tumor, trauma; (2) taking medications that may affect cognitive function; (3) combined with severe infectious and metabolic diseases; (4) combined with structural or functional damage of vital organs; (5) age < 18 years; and (6) no informed consent was signed.…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive function disorder ( n = 37) and normal cognitive function ( n = 107) patients were classified according to whether or not cognitive dysfunction occurred. The inclusion criteria were as follows: (1) Patients compatible with T2DM diagnostics criteria established by the ‘China Diabetes Prevention and Treatment Guideline (2017 Edition)”[ 11 ]; (2) patients who met the “Diagnostic Criteria of Lacunes” in the 2021 “Chinese Common Cerebrovascular Disease Medical Specialist Common Recognition” guidelines[ 12 ]; (3) routine blood tests performed on admission, and baseline data such as blood lipids and blood sugar levels were complete; and (4) head magnetic resonance imaging (MRI) was recorded on admission. The exclusion criteria were as follows: (1) Other intracranial diseases such as intracranial infection, massive cerebral infarction, cerebral hemorrhage, and tumor, trauma; (2) taking medications that may affect cognitive function; (3) combined with severe infectious and metabolic diseases; (4) combined with structural or functional damage of vital organs; (5) age < 18 years; and (6) no informed consent was signed.…”
Section: Methodsmentioning
confidence: 99%
“…Our results show that most CMBs amongst the cases were frequently noted in the cortical and subcortical regions, and this may explain the primary clinical observation of limb disorder. Indeed, Hou et al [49] recently confirmed that CMBs are associated with lower gait velocity, wider stride width, longer Time-up-and-Go (TUG) test times, and other upper and lower extremity dysfunctions amongst patients with CMBs.…”
Section: Discussionmentioning
confidence: 99%
“…CSVD is a type of lesion in which micro and small arteries, their distal branches, capillaries, microvessels, and small veins [1] are the main responsible vessels in the brain. This category also includes some hereditary CSVD, such as autosomal dominant disease combined with subcortical infarcts and leukoencephalopathy (CADASIL) and autosomal recessive disease combined with subcortical infarcts and leukoencephalopathy (CARASIL).…”
Section: The Concept and The Epidemiologic Featuresmentioning
confidence: 99%
“…Cerebral small vessel disease (CSVD) is a common manifestation of cerebrovascular disease that can seriously jeopardize one's health due to its insidious onset, mild clinical symptoms, and ease of neglect [1] . Early diagnosis can significantly reduce the mortality and disability of related cerebrovascular events.…”
Section: Introductionmentioning
confidence: 99%